Material didáctico reciclado para reforzar la motricidad fina en los niños de 3 años de la escuela de educación básica Lauro Damerval Ayora de la ciudad de Loja, periodo académico 2021- 2022 - Cuenca Orellana, Jessenia Stefania (2023)
Fine motor skills is a skill that involves the precise coordination of small muscles, bones, and nerves to produce precise movements that are required to perform everyday tasks. That is why the present curricular integration work aimed to determine the incidence of recycled teaching material for the development of fine motor skills in children of initial education I of the Lauro Damerval Ayora school in the city of Loja in the academic period 2021 -2022. Likewise, the research used a quantitative approach, with a quasi-experimental design and descriptive scope. The methods that were used for this study were the inductive-deductive and analytical-synthetic, in addition, a sample of 15 children was taken and the instrument that was applied was the Abbreviated Scale of Development (EAD-1) of Nelson Ortiz, where only We worked with the area of fine motor skills, obtaining in the initial results that 27% of children were found in an alert level and only 13% in a high level, reflecting that infants show clumsiness in their fingers and little control of the pincer. digital when carrying out activities such as: tearing, cutting, painting, coloring, inserting beads, among others. Due to the above, an alternative proposal called "My Creative and Fun World" was carried out with 40 activities; denoting a decrease to 7% in the alert level and an increase of 33% in the high level. Therefore, it is concluded that the recycled teaching material as a methodological strategy helps children to improve their fine skills. Keywords: bimanual coordination, recycled material, fine motor skills, types of didactic material.